GLP-1 and Its Role in Glycogen Production: A Narrative Review - Joseph Lotosky; Xavier Jean; Anungoo Altankhuyag; Saqib Khan; Ashley Bernotas; Alireza Sharafshah; Kenneth Blum; Alan Posner; Panayotis K. Thanos (Biomedicines, 2025)
Glucagon-like peptide-1 (GLP-1) has emerged as a pivotal regulator in the management of glucose homeostasis, glycogen metabolism, and energy balance, positioning it as a critical therapeutic target for addressing obesity, metabolic syndrome, and type 2 diabetes mellitus (T2DM). GLP-1 receptor agonists (GLP-1RAs) have shown promise for improving glycemic control and reducing weight through appetite regulation, delayed gastric emptying, and energy expenditure modulation. This narrative review explores the mechanisms of GLP-1-mediated glycogen metabolism and energy expenditure, particularly in key tissues—pancreas, liver, skeletal muscle, and adipose tissue. In the pancreas, GLP-1 enhances insulin secretion and beta-cell function. In the liver, it promotes glycogen synthesis via insulin-dependent and potential insulin-independent pathways, involving protein kinase B (AKT) and AMP-activated protein kinase (AMPK) signaling. Skeletal muscle benefits from GLP-1 through increased glucose uptake, AMPK activation, and mitochondrial function, facilitating glycogen storage. In adipose tissue, GLP-1 stimulates brown adipose tissue (BAT) thermogenesis and energy expenditure, contributing to weight loss. This increase in energy expenditure, along with enhanced glycogen metabolism, is a plausible mechanism for the weight loss observed with GLP-1RAs. Despite these advances, significant knowledge gaps remain, particularly regarding the direct hepatic effects of GLP-1, the extent to which it modulates glycogen metabolism in vivo, and its impact on thermogenesis in humans. Future research focusing on both the tissue-specific actions of GLP-1 and its systemic role in energy homeostasis and metabolic regulation will be essential for optimizing its therapeutic potential.